Online job search - Deva, Swetha (Kansas State University, 2008)
The aim of this project is to help students find a job that suits their profile. This provides a common platform for the job seekers to search for jobs on one website instead of searching them on multiple websites which highly reduces the time of searching for a suitable job. This website also provides a platform for the recruiters to post a job and search for the resume suitable to their job requirements. This website allows the job seekers to build a resume using resume builder (using this students can design their resume online), search for a job (search is based on different selection criteria like location, salary, job type, company, category etc), check apply history (can go through the list of jobs applied), create a search agent according to their priorities through which they can be updated with all the latest jobs posted on the website. This application also allows the recruiters to post a new job available in their organization, can search for resume and can schedule the interview if the person’s profile matches with the job requirements posted by the recruiter. This website is developed using ASP.NET 2005 and MS SQL SERVER 2005. The main goal in designing this website was to get familiar with .NET technology.
Keywords: Online Job Search; Computer Science (0984)